Effect of Dietary Supplementation with Different Levels of Arginine on Some Blood Traits of Laying Hens - Al-Hassani, Ali S.A. (International Journal of Poultry Science, 2011)
This experiment was carried out at the Field of Poultry, Department of Animal Resources, College of Agriculture, University of Baghdad during the period from 1/5/2011 until 5/7/2011 to study the effect of adding arginine to laying hens diet on certain blood traits. A total of 100 Brown Lohmann laying hens chicken, 38 weeks of age were randomly distributed on four treatment groups with 25 hens for each treatment. Treatment groups were: T1: Bird fed diet with no additional arginine (control group); T2, T3 and T4: Birds fed diet supplemented with 0.4, 0.7 and 0.9% respectively. Therefore, the total amounts of arginine in the four treatments (T1, T2, T3 and T4) become 1.1, 1.5, 1.8, 2.0% respectively. Results of this experiment revealed that there were no significant differences (p>0.05) between treatment groups regarding the total of Red Blood Cells Count (RBC) as well as with respect to each of the Hemoglobin concentration (Hb) and Packed Cell Volume (PCV). It was also noticed that there were no significant differences (p>0.05) between treatment groups concerning each of Mean Cell Volume (MCV), Mean Cell Hemoglobin (MCH) and Mean Corpuscular Hemoglobin Concentration (MCHC). Moreover, results of this study also denoted that supplementing ration of laying hens with different levels of arginine (T2, T3 and T4) resulted in significant increase (p